Guidlines for inventors “From idea to product” - Kaķis, Roberts; Blumberga, Dagnija; Vīgants, Ģirts (International Conference “Environmental Engineering”, 2020)
The article deals with the problem facing Latvian inventors in how to develop the idea to a real product. There are often cases where innovative ideas “migrate” from original inventors to other inventors, when they turn to them to seek support for developing and supporting the idea. The main components of the guidelines are the establishment of a patent application and, in general, a description of the entire patent acquisition process and the creation of a life cycle analysis using the SimaPro software. The article is intended primarily for the development of environmentally friendly inventions, which is why the life cycle analysis is one of the main components of the article, to make it possible to conclude whether the production and use of the new product will not result in a higher “ecological footprint” than previously used technologies, paying particular attention to the inventor stage in order to accurately develop a life-cycle analysis. The article does not only explore the necessary theoretical knowledge of the realisation of the idea to the product, but also looks at the pilot case, a practical example of an innovative “dust co-firing burner” compared to the conventional natural gas burner. The life-cycle analysis compares the following steps: manufacture of plants, transportation of plants and special emphasis on the combustion phase of fuels, three scenarios are examined: a natural gas burner burning natural gas, a dust burner in which natural gas is co-incinerated and fine wood particles − dust and a dust burner burning. biomethane and wood dust. The use of such an installation would not only reduce emissions from the replacement of natural gas by wood dust, but also allow energy companies to work more effectively, as it would be possible to regulate the proportion of different fuels depending on demand, because the fuels have different heat of combustion. The article establishes a methodology to analyse the quality and implementation of inventions in response to the following key questions: − how to identify original ideas and how to protect authors from the migration of ideas; − how to collect and analyse the risks associated with migration of ideas; − how to use life cycle analysis for the assessment of the “ecological footprint” of the invention.